Identification of ARKL1 as a Negative Regulator of Epstein-Barr Virus Reactivation - Siddiqi, Umama Z. (J Virol, 2019)
Epstein-Barr virus (EBV) maintains a life-long infection due to the ability to alternate between latent and lytic modes of replication. Lytic reactivation starts with derepression of the Zp promoter controlling BZLF1 gene expression, which binds and is activated by the c-Jun transcriptional activator. Here, we identified the cellular Arkadia-like 1 (ARKL1) protein as a negative regulator of Zp and EBV reactivation. Silencing of ARKL1 in the context of EBV-positive gastric carcinoma (AGS) cells, nasopharyngeal carcinoma (NPC43) cells, and B (M81) cells led to increased lytic protein expression, whereas overexpression inhibited BZLF1 expression. Similar effects of ARKL1 modulation were seen on BZLF1 transcripts as well as on Zp activity in Zp reporter assays, showing that ARKL1 repressed Zp. Proteomic profiling of ARKL1-host interactions identified c-Jun as an ARKL1 interactor, and reporter assays for Jun transcriptional activity showed that ARKL1 inhibited Jun activity. The ARKL1-Jun interaction required ARKL1 sequences that we previously showed mediated binding to the CK2 kinase regulatory subunit CK2β, suggesting that CK2β might mediate the ARKL1-Jun interaction. This model was supported by the findings that silencing of CK2β, but not the CK2α catalytic subunit, abrogated the ARKL1-Jun interaction and phenocopied ARKL1 silencing in promoting EBV reactivation. Additionally, ARKL1 was associated with Zp in reporter assays and this was increased by additional CK2β. Together, the data indicate that ARKL1 is a negative regulator of Zp and EBV reactivation that acts by inhibiting Jun activity through a CK2β-mediated interaction. IMPORTANCE Epstein-Barr virus (EBV) maintains a life-long infection due to the ability to alternate between latent and lytic modes of replication and is associated with several types of cancer. We have identified a cellular protein (ARKL1) that acts to repress the reactivation of EBV from the latent to the lytic cycle. We show that ARKL1 acts to repress transcription of the EBV lytic switch protein by inhibiting the activity of the cellular transcription factor c-Jun. This not only provides a new mechanism of regulating EBV reactivation but also identifies a novel cellular function of ARKL1 as an inhibitor of Jun-mediated transcription.